THE CONNECTION BETWEEN DRESSING AND DOMINANCE - Tóth Alexandrа (Collection of scientific papers «ΛΌГOΣ», 2023)
Introduction. Non-verbal communication plays a prominent role in human interactions, and dressing is one of the basic tools for this form of communication. The way we dress can affect how we interpret and value each other. In addition, the concept of dominance is also an important factor in human relationships, influencing our behaviour and our reactions to social situations.